2002
DOI: 10.2307/1562247
|View full text |Cite
|
Sign up to set email alerts
|

Coase's Penguin, or, Linux and "The Nature of the Firm"

Abstract: The emergence of GNU/Linux as a viable alternative to the Windows operating system and of the Apache webserver software as the leading web server have focused wide attention on the phenomenon of free or open source software. Most of the attention to the economic aspects of the phenomenon has been focused on the question of incentives-why, it is asked, would anyone invest effort in a productive enterprise in whose fruits they do not claim proprietary rights of exclusion-and has been devoted to studying this phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
730
0
81

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,149 publications
(817 citation statements)
references
References 0 publications
6
730
0
81
Order By: Relevance
“…Developers of open source software are known to self-assign to tasks based on their preferences and ability (Benkler, 2002;Bonaccorsi and Rossi, 2003;Yamauchi, et al, 2000) and they seek a creative challenge and fun when writing software (Lakhani and Wolf, 2005;Hertel et al, 2003). Yet, some essential tasks in open source software development are considered to be mundane and boring (Shah, 2006;von Hippel and Lakhani, 2003 found that newcomers to a project reused software they had written for other projects in order to make their first contributions.…”
Section: Research Gap: Open Source Software Knowledge and Code Reusementioning
confidence: 99%
“…Developers of open source software are known to self-assign to tasks based on their preferences and ability (Benkler, 2002;Bonaccorsi and Rossi, 2003;Yamauchi, et al, 2000) and they seek a creative challenge and fun when writing software (Lakhani and Wolf, 2005;Hertel et al, 2003). Yet, some essential tasks in open source software development are considered to be mundane and boring (Shah, 2006;von Hippel and Lakhani, 2003 found that newcomers to a project reused software they had written for other projects in order to make their first contributions.…”
Section: Research Gap: Open Source Software Knowledge and Code Reusementioning
confidence: 99%
“…4 Asimismo, Yochai Benkler proclama las virtudes del "patrimonio común basado en la producción entre pares." 5 La publicontratación ("crowdsourcing", en inglés) y otras actividades distribuidas similares surgen a partir de una identidad de comunidad no presencial y la refuerzan. La gente parece genuinamente motivada por la idea de que la inteligencia colectiva puede conseguir más que el logro de los individuos e investigadores como Benkler argumentan que tales modelos son más productivos que los sistemas de incentivos basados en el crédito personal que predominan en una variedad de lugares de trabajo.…”
Section: IIunclassified
“…Along these lines, in the following we describe the basic logics of peer production and open collaboration according to Yochai Benkler [3,4]. Benkler [4] claims that due to different drivers, peer-to-peer, nonmarket, and non-proprietary production may become not only possible, but the dominant form of production and organisation in the future.…”
Section: Introduction -Near-zero Marginal Costs and Neo-carbon Scenarmentioning
confidence: 99%